2009
DOI: 10.1103/physrevd.79.054012
|View full text |Cite
|
Sign up to set email alerts
|

Covariant light-front approach forBctransition form factors

Abstract: These predictions will be tested on the ongoing and forthcoming hadron colliders.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
149
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 37 publications
14
149
0
Order By: Relevance
“…The masses of quarks (in units of GeV) are used as [31][32][33][34][35][36][37][38][39] The β parameters in the wave functions of the doubly and singly heavy flavor baryons are approximately the same as those of the corresponding mesons, since the heavy-light diquark behaves a color antitriplet just like an heavy antiquark. Taking ++ cc as an example, β c[cu] ≈ β cc , which is the β parameter of η c .…”
Section: Numerical Results For Transition Form Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The masses of quarks (in units of GeV) are used as [31][32][33][34][35][36][37][38][39] The β parameters in the wave functions of the doubly and singly heavy flavor baryons are approximately the same as those of the corresponding mesons, since the heavy-light diquark behaves a color antitriplet just like an heavy antiquark. Taking ++ cc as an example, β c[cu] ≈ β cc , which is the β parameter of η c .…”
Section: Numerical Results For Transition Form Factorsmentioning
confidence: 99%
“…This approach has been widely applied to various mesonic transitions [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], and some analyses of baryonic transitions in this approach can be found in Refs. [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The LHCb collaboration has started comprehensive experimental studies of the decays [27], and some phenomenological studies can be found in refs. [28][29][30][31][32].…”
Section: Jhep12(2017)012mentioning
confidence: 99%
“…Some of them are: the nonrelativistic QCD [6,7], the Bethe-Salpeter relativistic quark model [8], the relativistic quark model [9][10][11], the light-cone QCD sum rules approach [12,13], the covariant light-front model [14], the nonrelativistic quark model [15], the QCD potential model [16][17][18], and the lightfront quark model [19]. The perturbative QCD (pQCD) [20,21] is one of the recently developed theoretical tools based on QCD to deal with the nonleptonic and semileptonic B decays.…”
Section: Br(b +mentioning
confidence: 99%